2015
DOI: 10.3928/02793695-20150923-04
|View full text |Cite
|
Sign up to set email alerts
|

Addiction to Work: A Critical Review of the Workaholism Construct and Recommendations for Assessment

Abstract: Workaholism was fi rst conceptualized in the early 1970s as a behavioral addiction, featuring compulsive use and interpersonal confl ict. The current article briefl y examines the empirical and theoretical literature over the past four decades. In relation to conceptualization and measurement, how the concept of workaholism has worsened from using dimensions based on anecdotal evidence, ad-hoc measures with weak theoretical foundation, and poor factorial validity of multidimensional conceptualizations is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 58 publications
4
80
0
9
Order By: Relevance
“…Some relevant literature reports that nursing is one among the professions at risk of work addiction [37]. A research conducted by Burke et al [38] used an ad hoc measuring scale to study workaholism in a sample of 496 Norwegian nurses.…”
Section: Workaholism and Nursingmentioning
confidence: 99%
“…Some relevant literature reports that nursing is one among the professions at risk of work addiction [37]. A research conducted by Burke et al [38] used an ad hoc measuring scale to study workaholism in a sample of 496 Norwegian nurses.…”
Section: Workaholism and Nursingmentioning
confidence: 99%
“…Over the past two decades, research examining work addiction has greatly increased (Clark, Michel, Zhdanova, Pui, & Baltes, 2016), both in terms of conceptual clarification and further consistent recognition regarding the correlates of work addiction (Andreassen, 2014;Atroszko, 2012;Griffiths, 2011;Shimazu, Schaufeli, Kamiyama, & Kawakami, 2015). Furthermore, many scholars have examined the differentiation between work addiction and work engagement as well as harmonious and obsessive passion towards work, both theoretically and empirically (e.g., Andreassen, 2014;Burke & Fiksenbaum, 2009;Birkeland & Buch, 2015;Karanika-Murray, Duncan, Pontes, & Griffiths, 2015;Karanika-Murray, Pontes, Griffiths, & Biron, 2015;Quinones & Griffiths, 2015;Quinones, Griffiths, & Kakabadse, 2016;Vallerand, Paquet, Philippe, & Charest, 2010;van Beek, Hu, Schaufeli, Taris, & Schreurs, 2012;van Beek, Taris, Schaufeli, & Brenninkmeijer, 2014). Studies have also demonstrated that the concepts are either slightly positively related (Shimazu & Schaufeli, 2009) or not at all (van Beek, Taris, & Schaufeli, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os participantes, 50,3% atuavam como profissionais liberais, 34,9% na prestação de serviços, 11,7% como vendedores e representantes comercias e 4,1% declararam-se somente como autônomos. A maioria recebia uma remuneração entre R$ 1.734,00 a R$ 7.475,00 (51,6%), faixa salarial definida como C, de acordo com a classificação da Fundação Getúlio Vargas (FGV)/ Centro de Politicas Sociais elaborada por Neri (2012).…”
Section: Laboraisunclassified